2002
DOI: 10.1124/dmd.30.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Desmethylnaproxen in the Rat—A Novel Acyl Glucuronide-Sulfate Diconjugate as a Major Biliary Metabolite

Abstract: This paper is available online at http://dmd.aspetjournals.org ABSTRACT:The nonsteroidal anti-inflammatory drug naproxen is primarily metabolized in humans by acyl glucuronidation to form naproxen acyl glucuronide and by O-dealkylation to form 6-O-desmethylnaproxen (DMN). DMN contains both carboxy and phenolic groups and has been shown to form acyl glucuronide and sulfate conjugates. This project aimed to investigate whether DMN formed a phenolic glucuronide and diglucuronide(s) (with both the carboxy and phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Diconjugates have been identified for other compounds. For example, an acyl glucuronide/sulfate conjugate of naproxen has been identified as a major biliary metabolite in male SD rats (Jaggi et al, 2002). Why HC from F-344 male rats form the diconjugate is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Diconjugates have been identified for other compounds. For example, an acyl glucuronide/sulfate conjugate of naproxen has been identified as a major biliary metabolite in male SD rats (Jaggi et al, 2002). Why HC from F-344 male rats form the diconjugate is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Fenselau and Johnson (1980) and Niemeijer et al (1991) reported that the O bond to the aromatic ring is not readily broken in the mass spectrometric analysis of phenols or phenol derivatives. The m/z 193 ion is considered to be the deprotonated glucuronic acid ion produced by cleaving the carboxyl group C-O bond, as reported by Jaggi et al (2002) and Plumb et al (2007) on the acyl O-glucuronides of desmethylnaproxen and ibuprofen. Given the mass spectrometric analysis and the fact that G2 is alkali-labile, this strongly suggests that G2 is the acyl O-glucuronide of T-5224.…”
Section: Discussionmentioning
confidence: 99%
“…Naproxen, a nonsteroidal anti-inflammatory agent, undergoes oxidative dealkylation to form 6-O-desmethyl naproxen. An acyl glucuronide-sulfate conjugate of this primary metabolite of naproxen was identified as a major biliary metabolite in male Sprague-Dawley rats (Jaggi et al, 2002). Efavirenz, a non-nucleoside reverse-transcriptase inhibitor of HIV-1, has also been shown to form a glucuronide-sulfate diconjugate in rat urine and bile (Mutlib et al, 1999).…”
Section: Glucuronide-sulfate Diconjugatesmentioning
confidence: 99%